Exploring the possibility of purification of water-alcohol solutions of different concentrations containing aldehydes and esters by mineral adsorbents - Marynchenko, Lolita; Marynchenko, Viktor; Hyvel, Mariana (Eastern-European Journal of Enterprise Technologies, 2017)
A comparative analysis of adsorption purification of water-alcohol solutions of different concentrations by clinoptilolite and shungite on the example of ethanol impurities such as acetaldehyde and ethyl acetate is carried out. Application of the aforementioned minerals for the adsorption of such simple substances as ethanol impurities is due to the previous positive results and the structure of the adsorbents investigated earlier. The optimum concentrations of water-alcohol solutions and the duration of contact of water-alcohol solutions with adsorbents for effective adsorption of aldehydes and esters are experimentally determined. The prediction of the efficiency of purification of polar impurities by mineral adsorbents based on the known rectification coefficients of the basic polar impurities is proposed. The higher the rectification coefficient, the lower the magnitude of hydrogen bonds of the impurity with ethanol and the easier it is to be sorbed from ethanol by mineral adsorbents. The relationship between the optimum concentration of water-alcohol solutions for effective adsorption of impurities and the rectification coefficient is shown. The expediency of using a mineral adsorbent such as clinoptilolite of Ukrainian origin instead of imported activated carbon in the production of alcoholic beverages is proved. It is determined that clinoptilolite is more useful as adsorbent for the purification of water-alcohol solutions containing aldehydes, which worsen the taste of alcoholic beverages most of all. It is shown that the use of clinoptilolite in the production of vodkas of underproof rectified alcohol will improve the taste of the final product.